2017
DOI: 10.5539/jas.v9n2p180
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and Efficacy of Chlorantraniliprole on Pieris rapae (Linnaeus) (Lepidoptera: Pieridae) on Cabbage

Abstract: Toxicity of chlorantraniliprole was assayed against young (first and second instars) and older larvae (third and fourth instars) of cabbage Pieris rapae (Lepidoptera: Pieridae) on cabbage (Brassicae oleracea), and persistence of field-aged leaf residue of chlorantraniliprole was assayed with 5-old-day larvae of P. rapae on cabbage. Efficacies of chlorantraniliprole and other newer insecticides to P. rapae were tested under field conditions for two seasons in Hubei province in China. The LC 50 value of chlorant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
(7 reference statements)
2
4
0
Order By: Relevance
“…The value of diamide seed treatments against lepidopteran and coleopteran insects has been shown for cyantraniliprole against Agrotis ipsilon and Mythimna unipuncta (Noctuidae) in maize 34,57 and chlorantraniliprole against Lissorhoptrus oryzophilus (Curculionidae) and Diatraea saccharalis (Crambidae) in rice 28,35,58 . In addition, consistent with our results, seed treatments using anthranilic diamide insecticides were efficacious against Delia platura (Diptera: Anthomyiidae) and Ostrinia nubilalis (Lepidoptera: Crambidae) in the snap bean, 59 and these compounds were selectively toxic to several other insect‐pest species 60–66 . The residual efficacy obtained here against FAW ( c .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The value of diamide seed treatments against lepidopteran and coleopteran insects has been shown for cyantraniliprole against Agrotis ipsilon and Mythimna unipuncta (Noctuidae) in maize 34,57 and chlorantraniliprole against Lissorhoptrus oryzophilus (Curculionidae) and Diatraea saccharalis (Crambidae) in rice 28,35,58 . In addition, consistent with our results, seed treatments using anthranilic diamide insecticides were efficacious against Delia platura (Diptera: Anthomyiidae) and Ostrinia nubilalis (Lepidoptera: Crambidae) in the snap bean, 59 and these compounds were selectively toxic to several other insect‐pest species 60–66 . The residual efficacy obtained here against FAW ( c .…”
Section: Discussionsupporting
confidence: 91%
“…wileyonlinelibrary.com/journal/ps efficacious against Delia platura (Diptera: Anthomyiidae) and Ostrinia nubilalis (Lepidoptera: Crambidae) in the snap bean, 59 and these compounds were selectively toxic to several other insect-pest species. [60][61][62][63][64][65][66] The residual efficacy obtained here against FAW (c. 14 days after plant emergence) was similar to the one against black cutworm, 34 and else the seed treatment was efficacious mainly in the early growth stages of rice and maize. 28,35,57,58 The route of insecticide application by the seed is generally safer for the environment and the operator, 67 but there are instances of side effects of systemic insecticides to beneficial zoophytophagous organisms.…”
Section: Discussionsupporting
confidence: 52%
“…Muthukrishnan et al (2013) reported that spinetoram at 45 and 54 g a.i./ha significantly reduced Spodoptera litura larval population in tomato. Chlorantraniliprole 52 mg a.i /L under field conditions was reported as effective as indoxacarb and spinosad furthermore significantly effective than emamectin benzoate in managing Pieris rapae giving marketable yield with three spray application (Su et al, 2017). Our results showed that insecticides viz., chlorpyriphos, deltamethrin, flubendiamide and lambda-cyhalothrin were less effective in controlling the larval DBM and CB population in cabbage.…”
Section: Discussionmentioning
confidence: 54%
“…Muthukrishnan et al (2013) reported that spinetoram at 45 and 54 g a.i./ha significantly reduced Spodoptera litura larval population in tomato. Chlorantraniliprole 52 mg a.i /L under field conditions was reported as effective as indoxacarb and spinosad furthermore significantly effective than emamectin benzoate in managing Pieris rapae giving marketable yield with three spray application (Su et al, 2017). Our results showed that insecticides viz., chlorpyriphos, deltamethrin, flubendiamide and lambda-cyhalothrin were less effective in controlling the larval DBM and CB population in cabbage.…”
Section: Discussionmentioning
confidence: 54%